Model Pendampingan UMKM Berbasis Analisis Perilaku untuk Pencegahan Food Waste: Pilot Project pada Jiji Kopitiam Semarang: Indonesia - Sari, Dewi Purnama; Wahyudan, Mohamad Bayu; Pradipta, Audrey; Kho, Herry Fernandes; Setyono, Hilda Fazira; Hermawanputri, Sarasifa Mashia; Nurdiyana, Kartika Ratih (UII, 2026)
Food waste is a significant challenge for culinary MSMEs due to weak raw material management and the absence of standardized operational procedures. This community service initiative aims to strengthen raw material management capacity to prevent overstock in the MSME pilot project, Jiji Kopitiam. The method consists of three stages: first, system analysis and intervention planning, which include problem identification and intervention design; second, program implementation; and third, the development of a sustainability plan. Root-cause analysis was conducted using a Fishbone diagram, while behavioral identification referred to the COM-B model to determine the behavioral change requirements. Intervention planning was developed using the Theory of Change and behavioural change identification to ensure that all activities followed a logical pathway toward the expected outcomes. The interventions included educational workshops, storage-layout simulations, the development of simplified SOPs, the strengthening of stock recording practices, and public educational campaigns. The results of the mentoring process indicate an improved understanding of raw material management among MSMEs, the adoption of labeling and reorganized storage practices, and increased awareness of systematic stock recording. The formulation of a sustainability plan further enhanced the likelihood of maintaining these improved practices. Overall, this mentoring program successfully fostered initial behavioral changes relevant to reducing food waste in culinary MSMEs.